COVID-19 Responsive Village: The Importance of Involving Persons with Disabilities - Imron, Dian Karinawati; Roidatua, Marthella Rivera (JSW (Jurnal Sosiologi Walisongo), 2021)
Persons with disabilities deal with complex challenges during the COVID-19 pandemic, especially those who live in the villages. The pandemic situation has brought limitations for persons with disabilities to get proper services both in health and social assistance. The strict regulation during COVID-19 became challenging for rural villages. Persons with disabilities as a vulnerable group is an essential part of inclusive development. This research aims to identify why involving persons with disabilities matters and analyze how rural villages implement inclusive development without 'leaving no one behind'. The method of the study is mixed-method. The result shows that involving persons with disabilities has significant impacts on the village development during pandemics. The study concludes that it is important to manage inclusive management both in village development and space provision for the organizations working with persons with disabilities to accommodate the needs and empowerment of the persons with disabilities._________The original draft of this article has been presented on the 6th International Conference on Social and Political Sciences (ICOSAPS) 2020: "Strengthening Resilient Society in the Disruptive Era" at Universitas Sebelas Maret Surakarta, Indonesia.